Non-Deterministic Finite Automata to Deterministic Finite Automata Conversion by Subset Construction Method using Python - Vayadande, Kuldeep; Patel, Krisha; Punde, Nikita; Patil, Shreyash; Nikam, Srushti; Pathrabe, Sudhanshu (International Journal of Computer Sciences and Engineering, 2022)
The theory of finite automata, formal languages and complexity are the modern branches in the field of computer theory and their mathematical models play a very important role in the practical world. This makes it really important, in theory as well as practice to translate a Non-deterministic Finite Automata (NFA) into a Deterministic Finite Automata (DFA). Many different approaches are developed for doing so. In this paper, an optimized algorithm for transition from NFA to DFA is given. This method is implemented using the programming language called python3. Along with this we have also used the pandas library of python for constructing the transition tables for NFA as well as DFA. A website for the same is also created to make it more user friendly by using the streamlit library of python.